Consideraciones económicas de los esquemas de vinculación de capital privado en la contratación estatal : contratación incompleta y regulación monopolística (2017)
"This paper deals with the legal phenomenon of public-private partnerships (PPPs) from an economic focus, trying to explore some thoughts which could be traced around this figure out of the Incomplete Contracting Theory and from literature on monopolistic regulation. Thus, the text is framed around a bid for the articulation of an application of economic analysis of law in a field that given its novelty ? since the more complete regulation of PPPs dates from 2012 with law 1508 ? has thus been insufficiently explored by local academics and whose comprehension could nourish from the interdisciplinary interaction between law and economics".-- Tomado del Formato de Documento de Grado.